ANALISISDRAFT UU KESETARAAN GENDER MENURUTPERSPEKTIF HUKUM ISLAM - , Muhammad Baskara Tri Nugraha, Zeni Luthfiyah (PARENTAL, 2014)
Abstract PlanLawJusticeandGenderEquality(Bill KKG) are now discussedopenly in theHouse of Representatives. Voicepro-cons startpopping up. We asMuslimshave achoicewhether toacceptorrejectthebillKKG. If thedraftbillrevisingtheMuslimsshouldrejectthe draftbill. Because,fundamentallydifferentconcepts inthe bill wascontrary tothe concepts ofIslamicprecepts. There area number of reasonsthatwerequire-as aMuslimandasan Indonesian-KKGrejectthisbill. Keywords: Analysis of the DraftLaw onGenderEquality, Perspectives onIslamicLaw